“Optimización en el proceso de pintura de las aeronaves en la Dirección de la Industria Aeronáutica de la Fuerza Aérea Ecuatoriana (DIAF) de la ciudad de Latacunga.” - Machay Catota, Alex Sebastián (2021)
This research project was carried out in the section for the picture of the company Directorate of the Aeronautical Industry of the Ecuadorian Air Force DIAF of the city of Latacunga, being the main economic activity of the DIAF the maintenance of civil aircraft and military, for which one of the main and final processes is the painting of the aircraft delivered by the maintenance center to the client, this process being taken into account as presentation and quality. The main objective of this project was focused on optimizing this process, since the company had a generalized and non-specific process, because of that a standard of time of the activities and productivity was unknown based on the resources in hand of work employees, affecting on several occasions compliance with maintenance planning. Based on the knowledge acquired in the industrial engineering career and with the guidance of the teaching staff, this work was carried out in the best way, mainly using the methodologies and techniques of method engineering. In the first phase, a survey of the initial state of the process was carried out, the results of which were represented in process, flow and path diagrams; then a time study was carried out in said state, to determine the standard of time and production; later an improved method was proposed, reducing standard time and increasing productivity. The improved method being standardized in a procedures manual for the DIAF aircraft painting process.